Distribution and seasonal abundance of Anopheline mosquitoes and their association with rainfall around irrigation and non-irrigation areas in Nigeria (UNED Research Journal, 2018)
The abundance of Anopheline mosquito species is the most common entomological measurement to determine the relationship between vectors and malaria incidence. We conducted an entomological survey to determine mosquito species diversity and abundance in relation to rainfall in Omi reservoir irrigation area, Nigeria. We collected adult mosquitoes from 10 randomly selected residential houses using Pyrethrum spray sheet and Human Landing Catch methods. We grouped the samples into irrigated (intervention) and non-irrigated (control) communities. During the 12-month sampling period, we collected a total of 4 285 mosquitoes belonging to 10 species in one family. The three most common species during this study were Anopheles gambiae, Anopheles funestus and Culex quinquefasciatus. Irrigated community has higher numbers of mosquitoes (69,4%) compared to those collected in non-irrigated community (32,0%). Comparing the two collection methods used, Pyrethrum spray sheet has a greater number 2 225(75,4%) of mosquitoes than those with Human Landing Catch method 724(24,6%). During dry season, we collected fewer mosquitoes. The lowest number was collected in February (114) and the highest occurring during the wet season in July (445).